Synthesis and characterization of aspirin-thiourea derivatives and their antibacterial activity - Choi, Ching Liang (Universiti Malaysia Sarawak (UNIMAS), 2015)
Thiourea and its derivatives have been actively studied in recent years mostly in their biological activities. This study focused on the synthesis and characterization of aspirinthiourea derivatives. The syntheses have been done via the reaction of acetylsalicyloyl chloride with series of amines. The long chains of amine formed by using 4-hydroxyl acetanilide and a series of bromoalkane have been synthesized. The synthesis aspirinthiourea derivatives were characterized by Fourier transform infrared spectroscopy (FTIR), 13C nuclear magnetic resonance (NMR) and 1H NMR spectroscopy. The antibacterial properties of the synthesized compound were determined by disc diffusion method against Escherichia Coli (E.coli). However, the newly synthesized aspirin-thiourea derivatives show intermediate antibacterial activity against E.coli. The effect of the structure of the compounds on antibacterial activity is discussed.